INTEGRASI MANAJEMEN PENDIDIKAN KARAKTER BERBASIS PESANTREN DALAM PENGUATAN KETERAMPILAN SOSIAL: STUDI KASUS MA DARUN NAJAH - Mohammad Syahrul Mubarok; Lilik Sri Hariani; Onik Farida Ni'matullah (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study analyzes the management strategies of pesantren-based character education in strengthening students' social skills at Madrasah Aliyah Darun Najah, Malang, amidst the moral degradation challenges of the digital era. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldana. The results indicate: (1) Educational planning is executed through the